Employment protection legislation and macroeconomic outcomes: channels of influence - Sordyl, Marta (Ekonomia i Prawo. Economics and Law, 2026)
Motivation: Employment protection legislation (EPL) plays an important role in shaping macroeconomic performance, yet its impact remains contested. Traditional analyses have focused on labour demand effects, but recent economic transformations call for a broader perspective. Globalization, technological change, and new labour market dynamics suggest that EPL may influence not only hiring and firing decisions but also productivity, innovation, income distribution and social welfare. Understanding these diverse channels is essential, as EPL can create opportunities while also generating rigidities that affect growth. Aim: This paper systematically examines the transmission channels through which EPL affects macroeconomic outcomes. It proposes a hierarchical framework in which the effects onlabour demand are supplemented by EPL’s impact on productivity and resource allocation; labour supply and economic activity; well-being and social welfare. The study investigates how these channels shape key outcomes such as employment, unemployment, income structures, aggregate demand, total factor productivity, and social inequalities. The analysis relies on mixed-method approach, combining a comprehensive review of literature with an empirical assessment of relationships between EPL and economic performance. Results: The findings confirm that labour demand is the dominant channel of EPL influence, but productivity, labour supply, and efficiency effects are also important in determining macroeconomic and social outcomes. EPL influences economic performance not only by regulating job security but also by shaping incentives for innovation, organizational change, and resources use. By integrating these wider mechanisms, the study provides a more comprehensive understanding of EPL’s role in the economy. It contributes to policy debates by highlighting that EPL should be assessed not solely in terms of labour market flexibility, but also with regard to its broader implications for efficiency, equity, and welfare.